2014
DOI: 10.1111/papr.12257
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Water Temperature, Apparatus, and Age to Children's Pain during the Cold Pressor Task

Abstract: These results provide critically important information about water temperature, apparatus, and child age on CPT pain responding. It informs design of future CPT studies and directs consideration of methodological variability and child age when interpreting study findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
(102 reference statements)
4
11
0
1
Order By: Relevance
“…Children's trait pain catastrophizing predicted self‐reported pain intensity and fear during the CPT, with greater levels of trait pain catastrophizing associated with increased pain and fear. Additionally, similar to previous research, child age was a significant predictor of child pain tolerance, with older children keeping their hand in the water for longer. Overall, the results of the present study highlight the importance of considering individual characteristics in understanding the experience of pain and that these differences may make an individual more or less susceptible to experiencing increased anxiety in the context of receiving information about the pain experience.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Children's trait pain catastrophizing predicted self‐reported pain intensity and fear during the CPT, with greater levels of trait pain catastrophizing associated with increased pain and fear. Additionally, similar to previous research, child age was a significant predictor of child pain tolerance, with older children keeping their hand in the water for longer. Overall, the results of the present study highlight the importance of considering individual characteristics in understanding the experience of pain and that these differences may make an individual more or less susceptible to experiencing increased anxiety in the context of receiving information about the pain experience.…”
Section: Discussionsupporting
confidence: 86%
“…Third, children in the current study ranged in age from 8 to 14 years, thereby spanning the developmental periods of late childhood to early adolescence. Recent research revealed differences in pain responses to the CPT as a function of child age and sex differences in pain outcomes that emerge in early adolescence around the onset of puberty, highlighting critical developmental changes that may be occurring across the age span of the present study. The importance of examining developmental differences in pain catastrophizing and parent responses to child pain has been highlighted in the literature.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A cold pressor test involving hand immersion into 0–10°C water is often used in psychology experiments to induce pain in adults and children. 52 Not surprisingly, hand immersion in 5°C water led to greater discomfort than with 8, 10, or 15°C, though no differences were observed across the 3 warmer conditions (see Fig. 2 ).…”
Section: Perceptual Responsesmentioning
confidence: 77%
“…It is not clear whether this procedure actually models a threat or activates a homeostatic temperature-regulating mechanism, which would not correspond to stress. In addition to its use as a pain inducer, which would generate ambiguity regarding its true effect on the body (Lazarus, 1963), since this task has not only been used to study stress, but constitutes a protocol of great tradition for the study of pain and plays a crucial role in the understanding of its mechanisms, assessment and management (Birnie, Parker, & Chambers, 2016). This would confirm the approaches of the critics in relation to the ambiguity in the effects produced by this task, making it difficult to interpret the results of the studies that include it as a protocol for stress induction.…”
Section: Cold Pressor Taskmentioning
confidence: 99%